Rotational malalignment after closed intramedullary nailing of femoral shaft fractures and its influence on functional outcome - Sharma, Yogesh; Mugdum, Girish G.; Prabhakara, Anjan (International Journal of Research in Medical Sciences, 2017)
Background: Rotational malalignment after closed intramedullary nailing of femoral shaft fractures is one of the most common complication. Data on functional outcome of such rotational malalignment particularly in an Asian population is lacking. This cross sectional study intends to determine the prevalence of rotational malalignment occurring after intramedullary nailing of femoral shaft fractures using CT scans and also compare this with femoral malrotation detected by clinical methods. The study also aims to analyze the effect of such femoral malrotation on functional outcome. Methods: 81 patients who underwent closed IM nailing of femoral shaft fractures were reviewed after fracture union. The rotational malalignment was measured using CT scans and clinical methods. CT based torsional deformity >15° were considered significant. Functional outcome was assessed using Harris hip score (HHS), lower extremity functional scale (LEFS) and WOMAC osteoarthritis index for knee. Results: On CT 30 (37%), 24 (29.6%) and 27 (33.33%) patients had rotational malalignment of <10°, 10°-14° and >15° respectively. This was independent of the fracture location, fracture type, implant design or metallurgy. The clinical method of assessing femoral rotation was less accurate (sensitivity 18.52% and specificity of 79.63%) as compared to CT method though not statistically significant. However LEFS (P=0.009) and WOMAC (P=0.033) scores were statistically poorer in patients with true rotational malalignment (≥15°). However no significant difference was noted between the groups in HHS. Patients with external and internal rotation deformities had comparable functional results. Conclusions: In this study, true rotational malalignment (>15°) after closed intramedullary nailing of femoral shaft fractures was found in 33.33% of patients. This is independent of fracture location, fracture type, implant design or implant metallurgy. Torsional deformities of femur >15° affect knee and lower limb function as a whole. External and internal rotational deformities perform equally.